Konsep Pengembangan Dalam Pendidikan Islam dI Era Society 5.0 - Hamsah, Yudi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This article contains the concept of development in Islamic education in the era of society 5.0. Talking about education is certainly one of the ideals of all human beings to increase their dignity as a moral human being. Through education we get a variety of knowledge consisting of social, economic, religious and so on. Education that is no less important is Islamic education, because in Islamic education we are taught how to be good human beings. In this era of society, we are supported by very adequate facilities and infrastructure, of course with the presence of gadgets that we can use to learn and teach without having to spend extra energy. With just a cellphone and internet quota, students can access all forms of education through electronic media. The presence of changing times certainly makes its own development for Islamic education. Keywords: Development, Islamic Education, Era of Society Abstrak Artikel ini memuat tentang konsep pengembangan dalam pendidikan Islam di era society 5.0. Berbicara mengenai pendidikan tentu merupakan salah satu cita-cita dari seluruh manusia untuk meningkatkan harkat dan martabat sebagai manusia bermoral. Melalui pendidikan kita mendapatkan berbagai ilmu pengetahuan yang terdiri dari sosial, ekonomi, agama dan lain sebagainya. Pendidikan yang tak kalah pentingnya adalah pendidikan Islam, karena dalam pendidikan Islam kita diajarkan bagaimana menjadi manusia yang baik. Di era society ini, kita di dukung oleh sarana dan prasarana yang sangat memadai, tentu dengan hadirnya gadget yang bisa kita manfaatkan untuk belajar dan mengajar tanpa harus mengeluarkan tenaga yang ekstra. Cukup dengan bermodal handphone dan kuota internetan, para pelajar sudah bisa mengakses segala bentuk pendidikan melalui media elektronik. Hadirnya perubahan zaman tentu membuat perkembangan tersendiri bagi pendidikan Islam. Kata Kunci : Pengembangan, Pendidikan Islam, Era Society